In silico comparison of genomic regions containing genes coding for enzymes and transcription factors for the phenylpropanoid pathway in Phaseolus vulgaris L. and Glycine max L. Merr - Reinprecht, Yarmilla; Yadegari, Zeinab; Perry, Gregory E.; Siddiqua, Mahbuba; Wright, Lori C.; McClean, Phillip E.; Pauls, Peter K. (Frontiers in Plant Science, 2013)
Legumes contain a variety of phytochemicals derived from the phenylpropanoid pathway that have important effects on human health as well as seed coat color, plant disease resistance and nodulation. However, the information about the genes involved in this important pathway is fragmentary in common bean (Phaseolus vulgaris L.). The objectives of this research were to isolate genes that function in and control the phenylpropanoid pathway in common bean, determine their genomic locations in silico in common bean and soybean, and analyze sequences of the 4CL gene family in two common bean genotypes. Sequences of phenylpropanoid pathway genes available for common bean or other plant species were aligned, and the conserved regions were used to design sequence-specific primers. The PCR products were cloned and sequenced and the gene sequences along with common bean gene-based (g) markers were BLASTed against the Glycine max v.1.0 genome and the P. vulgaris v.1.0 (Andean) early release genome. In addition, gene sequences were BLASTed against the OAC Rex (Mesoamerican) genome sequence assembly. In total, fragments of 46 structural and regulatory phenylpropanoid pathway genes were characterized in this way and placed in silico on common bean and soybean sequence maps. The maps contain over 250 common bean g and SSR (simple sequence repeat) markers and identify the positions of more than 60 additional phenylpropanoid pathway gene sequences, plus the putative locations of seed coat color genes. The majority of cloned phenylpropanoid pathway gene sequences were mapped to one location in the common bean genome but had two positions in soybean. The comparison of the genomic maps confirmed previous studies, which show that common bean and soybean share genomic regions, including those containing phenylpropanoid pathway gene sequences, with conserved synteny. Indels identified in the comparison of Andean and Mesoamerican common bean sequences might be used to develop inter-pool phen